Ashes to ashes: Intense fires extinguish populations of urban short-range endemics - Mason, L.; Bateman, Bill; Miller, B.; Wardell-Johnson, Grant (Blackwell Publishing Asia, 2018)
Native bushland fragmented by urbanization often experiences increased cover of flammable weeds, reduced biomass turnover and an absence of fuel management combined with increased ignitions. Depending on species’ mobility and dispersal traits, and the extent of burns within urban remnants, such fires may reduce individual survival rates or limit natural recolonization. We monitored the survival of mygalomorph spiders for a year following high-intensity and low-intensity fires in Banksia woodland remnants in urban Perth. Of the 257 burrows found, 115 spiders were confirmed to initially survive after intense wildfire, but none were confirmed alive after 12 months. In sharp contrast, only one spider from 103 observed burrows was confirmed dead after a low-intensity prescribed fire. As there were instances of our monitored mygalomorphs relocating a short distance following only low intensity fires, we also tested whether predation rates were higher in burnt than unburnt areas. Higher rates of predation were found in burnt areas, but this was strongly influenced by both site and predator type. We recommend further consideration of low-intensity prescribed fire as well as alternative fuel management approaches in urban remnants to better conserve mygalomorph spider populations and other taxa with limited dispersal and/or mobility capabilities.